2023
DOI: 10.1002/etc.5767
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Polystyrene Nanoplastics in the Liver and Intestine of Normal and High‐Fat‐Diet Juvenile Zebrafish

Juan Du,
Yanqiu Hu,
Zhi Li
et al.

Abstract: Nanoplastics (NPs) are widely found and threaten environmental and biological safety, because they do not degrade completely. We aimed to preliminarily explore the toxicity of NPs in obese children, as childhood obesity is a growing global health concern. As such, in this study, zebrafish were used as a vertebrate toxicological model to examine the hepatic lipid metabolism and gut microbiota in juvenile zebrafish exposed to 1000 μg/L PS NPs and high‐fat diet (HFD)using Raman spectroscopy, pathological examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, smaller MPs are more likely to enter the cellular and somatic circulations and accumulate in organs such as the liver. , Therefore, we chose nanoplastics as the subject of our study. In addition, some studies have shown that some hazardous substances in plastics, such as bisphenol A and Di (2-ethylhexyl), cause lipid metabolism disorders in mice. , Current research on the effects of MPs/NPs on the liver involves various model organisms, such as fish, mice, and lamb. However, further investigation is needed to determine whether PS-NPs can induce lipid metabolism disorder in mice and to investigate the specific underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, smaller MPs are more likely to enter the cellular and somatic circulations and accumulate in organs such as the liver. , Therefore, we chose nanoplastics as the subject of our study. In addition, some studies have shown that some hazardous substances in plastics, such as bisphenol A and Di (2-ethylhexyl), cause lipid metabolism disorders in mice. , Current research on the effects of MPs/NPs on the liver involves various model organisms, such as fish, mice, and lamb. However, further investigation is needed to determine whether PS-NPs can induce lipid metabolism disorder in mice and to investigate the specific underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%